Perlindungan Hak Nafkah Anak Pasca Perceraian: Perspektif Maslahat dan Undang-Undang Nomor 35 Tahun 2014 - Azuratun Nasuha; Pagar; Muhammad Iqbal Irham (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Post-divorce conditions frequently result in the neglect of children’s rights, particularly financial support, despite clear legal obligations imposed on parents. Children, as a vulnerable group, require both normative and practical protection to ensure their well-being and sustainable development. This article examines the protection of child support rights after divorce through an integrative analysis of maslahah (public benefit) and Law Number 35 of 2014 on Child Protection. A qualitative approach is employed by combining normative juridical analysis with limited empirical insights derived from interviews with legal practitioners, enabling a more contextual understanding of the gap between legal norms and their implementation. The findings reveal that although legal frameworks and Islamic principles consistently position child support as a mandatory responsibility—primarily borne by the father—its enforcement remains weak due to limited monitoring mechanisms, low legal awareness, and socio-economic constraints. From the perspective of maqasid al-sharia, the fulfillment of child support constitutes a fundamental effort to preserve life, intellect, and lineage, thereby reinforcing its urgency beyond formal legality. The novelty of this study lies in its integrative framework that bridges positive law and Islamic legal philosophy to strengthen child protection discourse. Strengthening enforcement mechanisms, enhancing institutional supervision, and internalizing ethical-religious values are essential to ensure a more just, effective, and sustainable protection of children’s rights.